PEDAGOGICAL SIGNIFICANCE OF USING DIGITAL TECHNOLOGIES IN PRESCHOOL EDUCATION (International Congress on Economics, Management and Business Studies, 2026)
This article analyzes the theoretical and practical foundations of using digital technologies in preschool education. The impact of information and communication technologies on child development, the necessity of improving teachers’ digital competence, and the importance of creating an innovative educational environment are discussed. The advantages and challenges of implementing digital technologies in preschool educational institutions are examined, and recommendations for improving educational quality are provided.
Keywords: Preschool education, digital technologies, innovative pedagogy, ICT, educational quality, digital competence.